A Comparison of Cost Accounting Systems for the Charging of Internal IT Services using the example of the Enterprise Applications Department within the Portfolio Company Heraeus - Bartmann, Helen (2021)
Fil: Bartmann, Helen. Universidad Nacional del Litoral. Facultad de Ciencias Económicas; Argentina.